Critical Boundaries of Activism in Public Relations in Pakistan: A Comparative Analysis of Effects of Professional Practices - Mudassir Mukhtar, Noshina Saleem,Stephen D. McDowell (JSSH, 2023)
This paper explores that how do professional and craft public relations practices affect department level of involvement to deal with the activist pressure in public and private sector organizations in Pakistan. The effects of role and model preferences in Pakistan are discussed in the light of assumptions of excellence theory of public relations.